The innovations in the Ottoman legal administration:The 16th century between theory and practice - El-Moghazi, Honey (AUC Knowledge Fountain, 2018)
The purpose of this study is to bring to light some of the most formative innovations in the Ottoman legal administration that unfolded by the 16th Century. It serves to macroscopically trace back some of the major developments that led to the crystallization of the Ottoman legal system and the state's administration of justice. This study thus aims to demonstrate the process of the making of Ottoman law through the early attempts of codifying a comprehensive legal code together with the creation of a unique form of "Ottoman Hanafism". Furthermore, it aims to examine the role of some of the state actors as well as the judiciary in giving rise to a bureaucratic system of administration in attempting to establish standardization and uniformity throughout the empire and in bringing in line all of the empire's provinces.